Effect of heat input on microstructure, wear and friction behavior of (wt.-%) 50FeCrC-20FeW-30FeB coating on AISI 1020 produced by using PTA welding - Ozel, Cihan; Gurgenc, Turan (Public Library Science, 2018)
In this study, AISI 1020 steel surface was coated in different heat inputs with (wt.-%) 50FeCrC-20FeW-30FeB powder mixture by using plasma transferred arc (PTA) welding method. The microstructure of the coated samples were investigated by using optical microscope (OM), scanning electron microscope (SEM), X-ray diffraction (XRD) and energy dispersive X-ray (EDS). The hardness was measured with micro hardness test device. The dry sliding wear and friction coefficient properties were determined using a block-on-disk type wear test device. Wear tests were performed at 19.62 N, 39.24 N, 58.86 N load and the sliding distance of 900 m. The results were shown that different microstructures formed due to the heat input change. The highest average micro hardness value was measured at 1217 HV on sample coated with low heat input. It was determined that the wear resistance decreased with increasing heat input.
Keywords: Composite Coatings; Hardfacing Alloys; Fe; Surface; Steel